Update: factors influencing heart rate variability–a narrative review - Sammito, Stefan; Thielmann, Beatrice; Böckelmann, Irina (Frontiers in Physiology, 2024)
Objective: Heart rate variability (HRV) is an important non-invasive marker for the assessment of an organism's autonomic physiological regulatory pathways. Lower HRV has been shown to correlate with increased mortality. HRV is influenced by various factors or diseases. The aim of this narrative review is to describe the current state of knowledge on factors influencing HRV and their significance for interpretation. Methods: The narrative review only included reviews, meta-analyses, and cohort studies which were published until 2021. HRV confounders were grouped into four categories (non-influenceable physiological factors, diseases, influenceable lifestyle factors and external factors). Results: The review found that HRV was decreased not only in non-influenceable physiological factors (e.g. age, gender, ethnicity) but also in connection with various number of acute and chronic diseases (e.g. psychiatric diseases, myocardial infarction, heart failure), influenceable lifestyle factors (e.g. alcohol abuse, overweight, physical activity), and external factors (e.g. heat, noise, shift work, harmful- and hazardous substances). Conclusions: In order to improve the quality of HRV studies and to ensure accurate interpretation, it is recommended that confounders be taken into account in future diagnostic measurements or measurements in the workplace (e.g. as part of health promotion measures) in order to counteract data bias.